2020
DOI: 10.1029/2019jc015526
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Turbulence at a Near‐Surface Temperature Front in the Arctic Ocean

Abstract: High-resolution ocean temperature, salinity, current, and turbulence data were collected at an Arctic thermohaline front in the Nansen Basin. The front was close to the sea ice edge and separated the cold and fresh surface melt water from the warm and saline mixed layer. Measurements were made on 18 September 2018, in the upper 100 m, from a research vessel and an autonomous underwater vehicle. Destabilizing surface buoyancy fluxes from a combination of heat loss to the atmosphere and cross-front Ekman transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
(73 reference statements)
3
11
0
Order By: Relevance
“…Observations of wind-front interactions in ice-free MIZs yield contrasting results between the studies. Under winter conditions near the Arctic MIZ, Koenig et al (2020) provide evidence of sustained turbulence by forced symmetric instabilities associated with downfront winds and heat loss from the surface layer, which extract potential vorticity from the water column at submesoscale fronts. Conversely, Brenner et al (2020) found that upfront winds lead to frontogenesis on time scales shorter than Ekman dynamics.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Observations of wind-front interactions in ice-free MIZs yield contrasting results between the studies. Under winter conditions near the Arctic MIZ, Koenig et al (2020) provide evidence of sustained turbulence by forced symmetric instabilities associated with downfront winds and heat loss from the surface layer, which extract potential vorticity from the water column at submesoscale fronts. Conversely, Brenner et al (2020) found that upfront winds lead to frontogenesis on time scales shorter than Ekman dynamics.…”
mentioning
confidence: 94%
“…However, it has been demonstrated by theory and models that submesoscale flows in MIZs interact with horizontal gradients in density to modify ML structure, ESSOAr | https://doi.org/10.1002/essoar.10504395.1 | Non-exclusive | First posted online: Thu, 24 Sep 2020 09:41:41 | This content has not been peer reviewed. manuscript submitted to JGR: Oceans et al, 2016;Lu et al, 2015;Manucharyan & Thompson, 2017), and by observations in the Arctic (Timmermans & Winsor, 2013;Koenig et al, 2020;Brenner et al, 2020) and more recently in the Antarctic (e.g. (Swart et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, symmetric instability can be sustained by down-front winds or destabilizing convection, which would favor a forward energy cascade. Increased turbulence, which may have been caused by forced symmetric instability, was observed along a front, which we would categorize as between an AW mixed layer and a stratified SW layer by Koenig et al (2020) in the Nansen Basin of the Arctic Ocean.…”
Section: Stepwise Subductionmentioning
confidence: 99%
“…Most of these studies additionally utilized a variety of instruments, such as a vessel‐mounted Acoustic Doppler Current Profiler (ADCP), a thermosalinograph, a conductivity‐temperature‐depth (CTD) rosette, water sampling, atmospheric observations, and reanalysis or model data. The survey durations ranged from a few hours (Archer et al., 2020; Tippenhauer et al., 2021; Wulff et al., 2016) to 1–1.5 days (von Appen et al., 2018; Brenner et al., 2020; Koenig et al., 2020; von Appen et al., 2020), with more comprehensive studies such as Hosegood et al. (2017), Mahadevan et al.…”
Section: Introductionmentioning
confidence: 99%